MAIN FRAME DESIGN OF PRE-ENGINEERED BUILDING - ADITYA DUBEY; AKSHATA SAHARE (International Journal of Innovations in Engineering Research and Technology, 2021)
Pre-Engineered building (PEB) is a new concept for the construction of single storey industrial building. The concept is versatile not only due to its quality pre-designing and prefabrication but also due to its timeefficiency and light weight. The concept of Pre-Engineered Building includes the technique of providing the best possible section according to the optimum requirements. This concept has many advantages over Conventional SteelStructure (CSB). And Pre-Engineered Building is efficient alternative to Conventional Steel Building.Inthispapermain frame of Pre-Engineered Structure of 12 m, 14m, 16m, 18m, 20m width & 6m Eave height have been analysed and designed by Staad pro to understand behaviour of PEB. The design is done by IS 800:2007, “Code of practice for General Construction in Steel Structures" as well as IS 875:1987(Part 1,2&3), "Indian Standard code of practice for loads on buildings and structures". Load case considered inmodelling are Dead load, imposedload & Wind load with the various combinations as specified in IS.